THE CONTRIBUTION OF YOUTUBE VIDEO TO STUDENTS’ SPEAKING ON ANALYTICAL EXPOSITION - Eka Wahyuni; Yustika Nur Fajriah; Lucky Rahayu Nurjamin (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2022)
This study aims to investigate how YouTube videos developed students’ speaking on analytical exposition in EFL classroom. To achieve this aim, a qualitative case study design was conducted in this research. The participants involved in this research were six students of class XI in a senior high school in West Java, Indonesia. The data were obtained from observations and document analysis. The data were analysed regarding two categorizations; (a) students’ general aspect of speaking and (b) the improvement of students’ speaking in analytical exposition. The results of this investigation showed that the teacher’s intensive guidance to students during their speaking classroom using YouTube media could contribute to gaining students’ better attainment in terms of general aspects of speaking and the genre move. This could eventually lead to a suggestion that to achieve the meaningful instruction, teachers have to intensively do controlling students’ learning activities during the use of any platforms of teaching.